THE INFLUENCE OF IMPLEMENTATION OF ELECTRONIC TICKETS, POLICY ISSUING PERMISSIONS DRIVING AND DISCIPLINE AGAINST TRAFFIC VIOLATIONS - Sutarno, Sutarno; Putriana, Lies; Miranda, Agustinus (International Journal of Economics and Management Research, 2022)
Traffic Unit (Satlantas) is an implementing element whose duties are responsible for carrying out police duties including in the field of traffic, which is the elaboration of professional technical capabilities which include regulation, guarding, escort, patrolling, public education, and traffic engineering, registration and identification of drivers or motorized vehicles, investigation of traffic accidents and law enforcement in the field of traffic, to maintain security, order, and smooth traffic. This study examined and analyzed the effect of ETLE, SIM issuance policies, and discipline on reducing traffic violations in 5 areas of DKI Jakarta province. This research was conducted on 100 vehicle users using the partial least squares data analysis technique. The results showed that the implementation of ETLE implementation reduced traffic violations; SIM issuance policy reduced traffic violations, and discipline reduced traffic violations